Web Vulnerability Through Cross Site Scripting (XSS) Detection with OWASP Security Shepherd - Wibowo, Ripto Mukti; Sulaksono, Aruji (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
Web applications are needed as a solution to the use of internet technology that can be accessed globally, capable of displaying information that is rich in content, cost effective, easy to use and can also be accessed by anyone, anytime and anywhere. In the second quarter of 2020, Wearesocial released information related to internet users in the world around 4.54 billion with 59% penetration. People become very dependent on the internet and also technology. This condition was also triggered due to the Covid-19 pandemic.One thing that becomes an issue on website application security is internet attacks on website platforms and we never expected the vulnerability. One type of attack or security threat that often arises and often occurs is Cross Site Scripting (XSS). XSS is one of Top 10 Open Web Application Security Projects (OWASP) lists.There are several alternatives that we can use to prevent cyber-attack. OWASP Security Shepherd can be used as a way to prevent XSS attacks. The OWASP Security Shepherd project allows users to learn or develop their manual penetration testing skills. In this research, there are several case examples or challenges that we can use as a simulation of the role of OWASP Security Shepherd to detect this XSS. The purpose of this paper is to conduct a brief and clear review of technology on OWASP Security Shepherd. This technology was chosen as an appropriate and inexpensive alternative for users to ward off XSS attacks.